Salsa dance and perceived mental health benefits: a servant leadership theory-driven study - Pablo A. Domene; Chelsey Lawson (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2019)
The purpose of the current study was to assess servant leadership dimensions, perceived mental health benefits, and correlations between the two following an eight-week servant leadership theory-driven salsa dance programme taught to novice learners at a West Midlands, UK university. Upon completion of the salsa dance programme (frequency = once per week, intensity = moderate-to-vigorous physical activity, time = 90 minutes, type = group-based Cuban style salsa dance), a paper questionnaire was administered to the participants to complete in person. The questionnaire contained 18 items related to servant leadership dimensions (authenticity, empowerment, humility, standing back, and stewardship) in terms of the teaching and learning of salsa dance and four items related to perceived mental health benefits (mood enhancement, self-confidence, skill mastery, and social well-being). Authenticity and stewardship were rated higher in females when compared to males. Differences were found between perceived mental health benefits in both females and males with mood enhancement rated highest in both genders. This is the first study we are aware of to have applied principles of servant leadership in the teaching of salsa dance as a leisure-time physical activity. Servant leadership may have facilitated the high perceived mental health benefits observed.